Ben Jonsons Volpone : An Unconventional and Innovative Jacobean Comedy (IIUC Studies, 2014)
Ben Jonsons Volpone (1605) is the best known, most performed and most studied of all of his Plays. Volpone, or The Fox, does not contain the traditional moral and broad themes of Shakespeare. Volpone, disguised as a didactic comedy, is actually an intelligent and cynical satire that compels the audience to rethink their moral expectations. In Volpone, Jonson was successful in combining three genres in order to create a new form of comedy. Volpone is a powerful moral study of human greed, foxy cunning, and goatish lust. It is not the traditional form of comedy. It is a play that takes on the form of a comical satire as well as a morality play. It also adapts the features of a fable, and in that it strives to teach a moral. This play puts a different twist on what people would expect from a comedy or morality play. But, more than a satire on the traditional morality, it is a satire on the type of drama that was prevalent. This article analyses how Jonson presents his audience with an unconventional way of approaching the subjects he is satirizing by creating a new form of comedy that embodies the aspects of all three genres. DOI: http://dx.doi.org/10.3329/iiucs.v8i0.20400 IIUC Studies Vol.8 December 2011: 27-38